Reconstruction Of Evidence-Based Policy Based On Tracer Study Governance To Improve The Quality Of Doctoral Programs In Law: Rekonstruksi Tata Kelola Tracer Study Berbasis Evidence-Based Policy Untuk Peningkatan Mutu Program Doktor Ilmu Hukum - Itok; Ananditya Satriatama; Ismawati Septiningsih (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
Improving the quality of higher education is a strategic aspect in the development of the Doctoral Program in Law at Sebelas Maret University (UNS). One of the important instruments in evaluating the effectiveness of study programs is the Tracer Study, which is the tracking of alumni footprints to assess the suitability of education with the world of work. However, the implementation of the Tracer Study at UNS still faces challenges, such as low alumni response, incomplete data, and lack of integration of results into academic policies. This research aims to develop an Evidence-Based Policy (EBP)-based Tracer Study model to improve the effectiveness of collection, processing, and utilization of alumni data. The research approach used is qualitative descriptive with the support of quantitative analysis. Primary data was obtained through interviews with academics, alumni, and policy makers, while secondary data was collected from Tracer Study reports, policy documents, and scientific literature. Data collection techniques include surveys, interviews, and documentation analysis. The results of this study are expected to produce a systematic and adaptive Tracer Study model, which can be used as a basis for academic decision-making, curriculum improvement, and service improvement for students and alumni. The research outputs include the publication of scientific articles in the Sinta 4 journal as well as recommendations for improving the governance of the Tracer Study within the UNS Doctoral Program in Law